Refractory gold treatment-state of the art and future challenges - Dunne, Robert (2012)
A review of the current 'state of the art' of refractory gold treatment will be provided. This will include a global perspective of refractory processes past and present and the location of currently operating plants. Some discussion on the challenges that face the refractory gold industry will also be provided.